Parathyroidectomy in asymptomatic primary hyperparathyroidism reduces carotid intima‐media thickness and arterial stiffness. (12th October 2015) - Cansu, Güven Barış; Yılmaz, Nusret; Özdem, Sebahat; Balcı, Mustafa Kemal; Süleymanlar, Gültekin; Arıcı, Cumhur; Boz, Adil; Sarı, Ramazan; Altunbaş, Hasan Ali
Summary: Objective: Although an International Workshop has suggested that cardiovascular assessment in asymptomatic primary hyperparathyroidism (PHPT) patients is not necessary, improvements in risk factors of subclinical atherosclerosis have been shown following parathyroidectomy. The objectives of this study were to determine whether parathyroidectomy in asymptomatic PHPT patients causes any change in carotid intima‐media thickness (CIMT), arterial stiffness [pulse wave velocity (PWV)] and soluble CD40 ligand (sCD40L) levels. Design: Prospective study evaluating female patients diagnosed with asymptomatic PHPT in a single centre over a 6‐month period. Patients: A total of 48 subjects were included: 17 hypercalcaemic (HC, mean age: 51 ± 8 years, Ca: 2·73 ± 0·17 mmol/l) and 16 normocalcaemic (NC, mean age: 58 ± 7 years, Ca: 2·30 ± 0·10 mmol/l) PHPT patients, and 15 healthy controls (mean age: 52 ± 4 years, Ca: 2·27 ± 0·07 mmol/l). Measurements: Biochemical tests, CIMT, PWV and sCD40L levels were compared at baseline and 6 months after parathyroidectomy (PTx). Results: At baseline, CIMT and PWV values in the HC and NC patients were higher than in the control group. While there was a significant reduction in CIMT (601 ± 91 μm vs 541 ± 65 μm, P = 0·006) and PWV (9·6 ± 1·8 vs 8·4 ± 1·5 m/s, P = 0·000) in the hypercalcaemic group at the end of the 6th month after PTx, no change was observed in normocalcaemic group ( P = 0·686 and P = 0·196 respectively). No differences were observed in sCD40L levels between patient and control groups or between baseline and 6 months in patients undergoing parathyroidectomy. Conclusion: Parathyroidectomy leads to an improvement in the structural and functional impairment associated with atherosclerosis in the vascular wall in asymptomatic hypercalcaemic PHPT patients.